THE ARCHITECTURE IMMANENCY AND PLACE ATTACHMENT CASE: AGA KHAN AWARD FOR ARCHITECTURE LOCAL MOSQUES WINNING PROJECTS - Nursanty, Eko; Husni, Fahd Diyar (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2020)
People are conducting their daily activities in Architectural space. The local community, which uses and gives meaning to that locality, turns the area into a place. Place Attachment is the place that has an emotional connection with the users. This research aims to identify the types and the roles of Place Attachment concerning the local community's religious needs, particularly the Muslim community. This study employs a qualitative research method by deductive literature review and big-data analysis to determine the emotional bonding manifested in the local community mosques' cultural immanence. The study looks into three Aga Khan Awards for Architecture winning projects to qualify the cases as a promising architecture selected by standard criteria. It discovers several tangible and intangible architectural elements inherited from generation to generation within a community, instituted on their sense of religiosity and the basic human need to connect with their Creator. Place Attachment strength and the uniqueness of architectural manifestation are directly related to those elements' immanency and regarded as the inherited DNA of a community.Â